Desulfurization of model oil using pyridinium-based ionic liquid - Nurul Umaira Nisa, Mazelan (2013)
Sulfur is the most abundant element found in crude oil. This paper contains the study on desulfurization of model oil by extraction with Pyridinium-based ionic liquids. The objective of the project is to determine the sulfur compound, dibenzothiophene (DBT) removal efficiency of pyridinium-based ionic liquids, 1-ethylpyridinium ethylsulfate, (EpyESO4) from model oil. In order to characterize the Pyridinium-based ionic liquids, the characterization process of [EpyESO4] was conducted by using fourier transform infra-red (FTIR) analyzer. Lab testing on desulfurization has been done by using different concentration of DBT (100ppm and 1000ppm) at 10 minutes of extraction time. The efficiency of the removal process has been determined using high performance liquid chromatography (HPLC). From the result, [EpyESO4] shows high efficiency in remove aromatic sulfur compound (DBT) at low concentration of sulfur content. The percentage sulfur removal from the model oil for 100ppm and 1000ppm were, 97.68% and 26.68% respectively. By considering these results, [EpyESO4] might be used as promising solvents for the extractive desulfurization of diesel.